2014
DOI: 10.3109/03008207.2014.923881
|View full text |Cite
|
Sign up to set email alerts
|

Superposition of nanostructures on microrough titanium–aluminum–vanadium alloy surfaces results in an altered integrin expression profile in osteoblasts

Abstract: Recent studies of new surface modifications that superimpose well-defined nanostructures on microrough implants, thereby mimicking the hierarchical complexity of native bone, report synergistically enhanced osteoblast maturation and local factor production at the protein level compared to growth on surfaces that are smooth, nanorough, or microrough. Whether the complex micro/nanorough surfaces enhance the osteogenic response by triggering similar patterns of integrin receptors and their associated signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
3
22
0
1
Order By: Relevance
“…Here, the integrin β3 silencing resulted in a concomitant decrease of the integrin αv gene expression only in cells cultured on nanotopography. Corroborating this finding and our observation of the key role of integrin β3 in the osteogenic induction of Ti with nanotopography, it has been shown that the integrin αvβ3 complex is upregulated on nanostructured surfaces …”
Section: Discussionsupporting
confidence: 74%
“…Here, the integrin β3 silencing resulted in a concomitant decrease of the integrin αv gene expression only in cells cultured on nanotopography. Corroborating this finding and our observation of the key role of integrin β3 in the osteogenic induction of Ti with nanotopography, it has been shown that the integrin αvβ3 complex is upregulated on nanostructured surfaces …”
Section: Discussionsupporting
confidence: 74%
“…There have been many studies describing various nanostructures on titanium materials, and most of them have reported positive effects on osteoblast proliferation 39) . The superposition of nanoscale structures (pore diameter ranged between 20 nm and 180 nm) on a microrough surface (Sa=2.20) has been reported to provide the original surface with additional benefits including the enhancement of osteogenic gene expression 46) and modification of the expression profile of integrin subunits 47) of osteoblasts. Wettability has also been identified as an important factor affecting the control of osteogenic cell differentiation 48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…However, others have found that Noggin suppression resulted in poorer BMP2-induced osteogenesis [43]. The ultimate outcome may also be influenced by surface nanotopography [44], the response of other cell types around the implant to BMP2, and prove to be context-dependent. Moreover, a number of mechanisms may be responsible for an apparent BMP2 enhancement when MSCs are cultured on microtextured Ti, including the expression of microRNAs that influence BMP2 pathways [4547].…”
Section: Discussionmentioning
confidence: 99%